2010
DOI: 10.1016/j.virol.2010.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Replication-independent activation of human plasmacytoid dendritic cells by the paramyxovirus SV5 Requires TLR7 and autophagy pathways

Abstract: The paramyxovirus Simian Virus 5 (SV5) is a poor inducer of interferon (IFN) secretion in all cell types tested so far, including primary epithelial cells and primary human myeloid dendritic cells. SV5 is hypothesized to limit induction of antiviral responses through control of viral gene expression and production of the V protein antagonist. Plasmacytoid dendritic cells (pDCs) are known to uniquely express toll-like receptor (TLR)-7 and are a main producer of IFN-alpha among peripheral blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 46 publications
0
26
1
Order By: Relevance
“…While intriguing, this would be inconsistent with previous work showing that PIV5 is unable to block signaling through Toll-like receptors [65,67] or RIG-I [68]. These disparate findings may reflect differences in the targeting of TBK-1 pathways in different cell types, including cell lines versus primary cells.…”
Section: Paramyxovirus Interactions With Intracellular Rna-sensing Pacontrasting
confidence: 56%
See 1 more Smart Citation
“…While intriguing, this would be inconsistent with previous work showing that PIV5 is unable to block signaling through Toll-like receptors [65,67] or RIG-I [68]. These disparate findings may reflect differences in the targeting of TBK-1 pathways in different cell types, including cell lines versus primary cells.…”
Section: Paramyxovirus Interactions With Intracellular Rna-sensing Pacontrasting
confidence: 56%
“…This finding could account for the profound suppression of IFN-α production from MeV-infected pDC [64]. It is note-worthy that some paramyxoviruses fail to inhibit TLR-7-mediated IFN-α production during infection of pDC [65]. …”
Section: Paramyxovirus Interactions With Intracellular Rna-sensing Pamentioning
confidence: 99%
“…Measles virus, which, like NDV, belongs to the family Paramyxoviridae, induces autophagy through a pathogen receptor CD46-Cyt-1/GOPC pathway (18). Another paramyxovirus, parainfluenza virus type 5 (PIV5), requires autophagy pathways to activate human plasmacytoid dendritic cells (19). In the present study, we demonstrated that autophagy is induced upon NDV infection of chicken cells and tissues.…”
mentioning
confidence: 56%
“…(Manuse et al, 2010) One paramyxovirus, Human Parainflueza Virus 3 (HPIV3), specifically inhibits autophagosome maturation during infection. The virus encodes a protein, P, which is central to viral RNA replication.…”
Section: Induction Of Autophagic Signaling Vs Bona Fide Autophagymentioning
confidence: 99%